Synthesis of ladder diagrams in the control of the transport line of rolling elements - Adam Szcześniak; Zbigniew Szcześniak; Leszek Cedro (Archives of Control Sciences, 2025)
The article presents a synthesis of ladder diagrams in controlling any configuration of the conveyor path for delivering rolling elements to spiral storages in interoperative transport. The ladder diagram of the sequential control system sets the state of distributors to ensure a flow of parts to serve successive storages. The fundamental module of the ladder diagram is the memory block. The ladder diagram of the sequential control system was developed based on the sequence graph of filling the storages. A single or dual sensor system controls the filling status of spiral storages. The rolling element displacement control sensors work together with appropriately designed systems to execute the delay of the rising and falling edge input signal. Time-delay relays, specifically the ON-delay Timer and OFF-delay Timer, were used in programming PLC controllers to implement control systems. By using a two-level control of the filling level of the storages, it is possible to control the emptying status of the storages as a function of the technological time of removal of the items from the storage between the two control points. The synthesis of ladder diagrams in control and their verification was conducted using the computer program FluidSim by Festo.